Employment equity targets: How a state-owned enterprise recruits people with disabilities - Natasha Maclean; Martha Geiger; Lieketseng Ned (SA Journal of Human Resource Management, 2024)
Orientation: There remains a gap in the employment of people with disabilities globally. With its well-defined legislative framework, South Africa’s compliance with legislation still appears to have failed to ensure that employment targets are met across sectors.